Epidemiologic Evidence to Guide the Understanding and Prevention of Gun Violence. (10th February 2016) - Webster, Daniel W.; Cerdá, Magdalena; Wintemute, Garen J.; Cook, Philip J.
Abstract : Gunfire from assaults, suicides, and unintentional shootings exacts an enormous burden on public health globally. The epidemiologic reviews in this special issue enhance our understanding of various forms of gun violence, inform interventions, and help chart directions for future research. The available science, however, is limited to answer many important questions necessary for mounting successful efforts to reduce gun violence. Certain data are lacking, and there are numerous analytical challenges to deriving unbiased estimates of policy impacts. Significant investments in research over the long term are warranted to answer questions central to successful prevention of gun violence.